2015
DOI: 10.1371/journal.pone.0123568
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Lactate Dehydrogenase Levels with Laboratory Variables in the Clinical Severity of Sickle Cell Anemia in Congolese Patients

Abstract: BackgroundSickle cell anemia is an inflammatory disease and is characterized by chronic hemolysis. We sought to evaluate the association of lactate dehydrogenase levels with specific clinical phenotypes and laboratory variables in patients with sickle cell anemia.MethodsThe present cross-sectional study was conducted in Sickle Cell Centre of Yolo in Kinshasa, the Democratic Republic of Congo. Two hundred and eleven patients with Sickle Cell Anemia in steady state were recruited. Seventy-four participants with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…Anemia can have serious consequences for both women of reproductive age [ 2 , 3 , 4 ] and children [ 5 , 6 ]. Causes of anemia in the DRC include malaria [ 7 ], parasitic helminths and other infections [ 8 ], as well as sickle cell Hb [ 9 , 10 ]. Iron, folate, vitamin B12, vitamin A, zinc, and other micronutrient deficiencies can also contribute to anemia [ 11 ]; however, little is known about the micronutrient status of Congolese women of reproductive age and their young children [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anemia can have serious consequences for both women of reproductive age [ 2 , 3 , 4 ] and children [ 5 , 6 ]. Causes of anemia in the DRC include malaria [ 7 ], parasitic helminths and other infections [ 8 ], as well as sickle cell Hb [ 9 , 10 ]. Iron, folate, vitamin B12, vitamin A, zinc, and other micronutrient deficiencies can also contribute to anemia [ 11 ]; however, little is known about the micronutrient status of Congolese women of reproductive age and their young children [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other indicators of disease severity are bilirubin, PCV, erythropoiesis rate, leukocytes, LDH, fetal hemoglobin, creatinine, proteinuria, reticulocytes, HSV, phenotypes, days of hospitalization per year, severe vaso-occlusive crisis per year, number of transfusions per year, hip disease, leg ulcer, hepatobiliary complications, neurological events, renal disorders and body mass index [84,[119][120][121][122][123].…”
Section: Clinical Consequences Of the Presence Of Hb Smentioning
confidence: 99%
“…These studies have demonstrated a correlation between the serum LDH level and other markers of hemolysis such as bilirubin. 23 Also, red blood cell (RBC) count and haemoglobin (Hb) concentration alters in hemolysis. The identification of LDH may be considered as marker of hemolysis and might be an important tool for the early detection of the severity of the disease in HbS patients.…”
Section: Introductionmentioning
confidence: 99%